Principles of Direct and Database Marketing - Tapp Alan (Financial Times - Pitman Publishing, 1998)
This comprehensive text covers all aspects of direct and database marketing. Introducing Direct Marketing, What is Direct Marketing, The Database, Using Direct Marketing to Analyze the Marketing Situation, The Customer Database: Analysis and Applications, Using External Databases in Direct Marketing, Setting Objectives and Strategies within Direct Marketing, Direct Marketing Objectives and Strategies, The Internet, The Strategic Influences on Direct Marketing, Direct Marketing Implementation and Control, Offers and Incentives in Direct Marketing, Direct Marketing Media, Acquisition Media, Direct Marketing Creative Practice, Testing Budgeting and Research in Direct Marketing, Index.